-31+8x=29+6x

Simple and best practice solution for -31+8x=29+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -31+8x=29+6x equation:


Simplifying
-31 + 8x = 29 + 6x

Solving
-31 + 8x = 29 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-31 + 8x + -6x = 29 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-31 + 2x = 29 + 6x + -6x

Combine like terms: 6x + -6x = 0
-31 + 2x = 29 + 0
-31 + 2x = 29

Add '31' to each side of the equation.
-31 + 31 + 2x = 29 + 31

Combine like terms: -31 + 31 = 0
0 + 2x = 29 + 31
2x = 29 + 31

Combine like terms: 29 + 31 = 60
2x = 60

Divide each side by '2'.
x = 30

Simplifying
x = 30

See similar equations:

| y=29-4(6) | | 4sin^2x+2=5 | | y=29-4(5) | | X(3x+2)=23 | | y=29-4(4) | | 4/5=x-3/9 | | 7[x+(11)]+(-3)=-53 | | 2/5(d-3)=30 | | y=29-4(1) | | 6x-30=x-25 | | 9g-15=21 | | 3.4x=1.8x+2.5 | | 5x-6+2x=9x-7 | | 9j^2+42j+49=0 | | 3x^2+15x-9.1=0 | | h=3(1)+1 | | 0.2c+0.08c-3.6c=0 | | 9=9-11x | | 0.3(y+2)=24 | | 10z^2-1440=0 | | 28-2u=5u | | 2x+14=-5x-11 | | -5/4m-1/6=7/3 | | 4x-2=7-2x | | 8+3x-9x=20 | | 0=1-x+y | | 12x+3x-7=4x+31 | | 3x+3*(-3)=3 | | 5x+8+x=170 | | h=3(0)+1 | | 3x+3*3=3 | | -16h^2-49h-3=0 |

Equations solver categories